Serum calprotectin as promising diagnostic aid in predicting relapse in proteinase 3-antineutrophil cytoplasmatic antibodies-associated vasculitis - Van Hoovels, Lieve; Bossuyt, Xavier (Journal of Laboratory and Precision Medicine, 2017)
The recently published article of Pepper and colleagues (1) focuses on the deficit in diagnostic aids for predicting recurrent disease in antineutrophil cytoplasmatic antibodies (ANCA)-associated vasculitis (AAV). Although the diagnostic value of ANCA in AAV is well established and undisputed, the clinical benefit of ANCA for disease monitoring seems to be limited to targeted determination in patients clinically suspected for relapse (2,3), in patients with renal disease (4), and in patients that received plasmapheresis for severe AAV (5).